An evaluation of (Malawi Zebu) beef bull performance testing at Chitedze central testing station - Kasowanjete, M.B.B. (1977)
The Malawi Zebu beef bull performance testing scheme was evaluation in relation to growth rate and food conversion ration within 120 days. Descriptions and data on validity of the testing scheme and desirability of traits; correlation between the two and heritability of each; need for corrections for other variables; genetic improvement attained; and impacts of the selection exercise on the overall national beef industry included.